Australia’s maritime intentions : to expand or not to expand? - Till, Geoffrey (2014)
The October 2013 Australian fleet review illustrates naval trends in the Indo-Pacific and shows that Australia is currently set on a strategic policy of maritime expansion and forward engagement. There are, however, doubts about Canberra’s future defence spending under an Abbott government.